SunHorizon advanced control system and proactive maintenance tool: Case study in Latvia - Martín-Crespo , Alejandro; Hernández-Serrano , Alejandro; Arnanz, Roberto; Belda-González , Alberto; Gabaldón Moreno , Andrea (CLIMA 2022 conference, 2022)
Currently, buildings represent a large percentage of the energy consumption in the European Union. Increasing the introduction of renewable energy sources is becoming necessary to achieve an effective reduction of greenhouse gas emissions. SunHorizon project demonstrates the potential of combining solar appliances and heat pumps in buildings for meeting heating and cooling (H&C) demands in Europe. The energy systems are managed by an advanced Python-based control system. Using the forecast of the demand and occupancy of the building, a predictive controller calculates the optimal exploitation of resources and storage use in order to maximize the renewable energy use and cost performance. Furthermore, the control system operates in combination with a proactive maintenance tool that includes fault detection and maintenance surveillance capabilities. This tool is based on the Reliability-Centred Maintenance (RCM) strategy, which focuses on understanding the equipment failure modes, applying all the different possible maintenance strategies and considering consequences and cost of failures. To achieve this goal, several key performance indicators (KPIs) are defined, calculated in real-time operation and compared with simulation data to detect faults. When any failure is obtained, the system triggers specific alarms via web and email, hence notifying house operators or final users. KPIs are also evaluated to calculate their remaining useful life (RUL) and therefore predict future faults. The solution is applied in a building in Riga (Latvia) and the methodology beneath these tools is explained in this paper. The use of prediction for control and maintenance will allow the system to avoid wasting energy, increase self-consumption as well as to save costs on the energy bills.